Alternative cash transfer delivery mechanisms: Impacts on routine preventative health clinic visits in Burkina Faso - Richard Akresh; Damien de Walque; Harounan Kazianga (Institute for the Study of Labor (IZA), 2012)
We conducted a unique randomized experiment to estimate the impact of alternative cash transfer delivery mechanisms on household demand for routine preventative health services in rural Burkina Faso. The two-year pilot program randomly distributed cash transfers that were either conditional or unconditional and the money was given to either mothers or fathers. Families enrolled in the conditional cash transfer schemes were required to obtain quarterly child growth monitoring at local health clinics for all children under five years old. There was not such a requirement under the unconditional programs. Compared with control group households, conditional cash transfers significantly increase the number of preventative health care visits during the previous year, while unconditional cash transfers did not have such an impact. For the conditional cash transfers, money given to mothers or fathers showed beneficial impacts of similar magnitude in increasing routine visits.
urn:nbn:de:101:1-2012042310526
Keywords: I15; I38; J13; O15; 330; cash transfers; conditionality; gender; child health; Africa; Gesundheitsversorgung; Privater Haushalt; Sozialtransfer; Gesundheitsvorsorge; Ländlicher Raum; Burkina Faso